Spatial relationships between alcohol-related road crashes and retail alcohol availability. (1st May 2016) - Morrison, Christopher; Ponicki, William R.; Gruenewald, Paul J.; Wiebe, Douglas J.; Smith, Karen
Highlights: Spatial relationships with crashes differ for bars and off-premise outlets. Motor vehicle crashes are positively related to bar density in adjacent areas. Spatial analyses must consider origins and destinations of alcohol-affected journeys. Abstract: Background: This study examines spatial relationships between alcohol outlet density and the incidence of alcohol-related crashes. The few prior studies conducted in this area used relatively large spatial units; here we use highly resolved units from Melbourne, Australia (Statistical Area level 1 [SA1] units: mean land area = 0.5 km 2 ; SD = 2.2 km 2 ), in order to assess different micro-scale spatial relationships for on- and off-premise outlets. Methods: Bayesian conditional autoregressive Poisson models were used to assess cross-sectional relationships of three-year counts of alcohol-related crashes (2010–2012) attended by Ambulance Victoria paramedics to densities of bars, restaurants, and off-premise outlets controlling for other land use, demographic and roadway characteristics. Results: Alcohol-related crashes were not related to bar density within local SA1 units, but were positively related to bar density in adjacent SA1 units. Alcohol-related crashes were negatively related to off-premise outlet density in local SA1 units. Conclusions: Examined in one metropolitan area using small spatial units, bar density is related to greater crash risk in surrounding areas. Observed negative relationships for off-premise outlets may be because the origins and destinations of alcohol-affected journeys are in distal locations relative to outlets.